2003
DOI: 10.1046/j.1471-4159.2003.02076.x
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of neuronal 5‐HT7 receptors to activation of extracellular‐regulated kinase through a protein kinase A‐independent pathway that can utilize Epac

Abstract: The roles of 3¢,5¢-cyclic adenosine monophosphate (cAMP) and protein kinase A in 5-hydroxytryptamine (5-HT) 7 receptormediated activation of extracellular-regulated kinase (ERK) were studied in cultured hippocampal neurons and transfected PC12 cells. Activation of ERK by neuronal G s -coupled receptors has been thought to proceed through a protein kinase A-dependent pathway. In fact we identified coupling of 5-HT 7 receptors to activation of adenylyl cyclase and protein kinase A. However, no inhibition of ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
89
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 37 publications
7
89
1
Order By: Relevance
“…It is also possible, however, that PKC and MEK are part of the same pathway and one is downstream of the other. At present, there is no evidence that activation of Epac by cAMP can lead to direct activation of MEK/ERK pathway in vitro (Enserink et al, 2002;Lin et al, 2003;Gelinas et al, 2008). Consistently, we observed a small 8-pCPTinduced increase in p-ERK in GRK2-deficient cells but not in WT cells.…”
Section: Discussionsupporting
confidence: 81%
“…It is also possible, however, that PKC and MEK are part of the same pathway and one is downstream of the other. At present, there is no evidence that activation of Epac by cAMP can lead to direct activation of MEK/ERK pathway in vitro (Enserink et al, 2002;Lin et al, 2003;Gelinas et al, 2008). Consistently, we observed a small 8-pCPTinduced increase in p-ERK in GRK2-deficient cells but not in WT cells.…”
Section: Discussionsupporting
confidence: 81%
“…It has been shown that serotonin activates ERK1/2 kinases through 5-HT1A receptors in cultured human peripheral blood mononuclear cells, 24 and through 5-HT1B in neuroblastoma cells. 25 In smooth muscle cells, 26,27 mesangial cells 7,28 and PC12 cells 29 30 Serotonin-stimulated 5-HT7 receptors were found to activate ERK1/2 kinases in hippocampal neurons, 31 in COS-7 and HEK293 cells. 32 Upon stimulation, ERK1/2 are phosphorylated and translocate to the cell nucleus where they can phosphorylate and activate transcription factors including c-Myc, 33 and ELK or, through the cytoplasmic kinase p90Rsk, the transcription factor cAMP response binding protein (CREB).…”
Section: Research Papermentioning
confidence: 99%
“…cAMP causes in turn activation of MAPK such as the extracellular-regulated kinase (ERK1/2; Lin et al, 2003). In addition, there is evidence that 5-HT7R can also activate PKC indicating that the same receptor may contribute to different signaling pathways besides the canonical PKA downstream pathway (Lieb et al, 2005).…”
Section: Mapk Dependent Pathwaymentioning
confidence: 99%